Calculation of PIT 4 Coal Reserves with Cross-Cross Method - Shabiruddin Shabiruddin; Anshariah Anshariah; Hasbi Bakri (CV Insight Publisher, 2022)
Calculating coal reserves using the vertical section method can describe the condition of deposits and overburden in each section. This study aimed to determine the direction of coal distribution, the volume of overburden, and the volume of coal using the cross-section method and to obtain the stripping ratio (SR). In this research activity, data is needed in the form of documentation on pit 4, cross-section, drill logs, and coordinates of drill points. After all the data has been collected, it is continued by making a cross-section in the form of a horizontal (cross-section) using Auto Cad software. The final stage of the interpretation of the two data results is calculating the number of coal reserves, the amount of overburden (OB), and the stripping ratio value by the concept of continuity that has been carried out from the existing data.